Hydrometallurgical process for separation and recovery of product from serpentine waste. (September 2013) - Zhu, P.; Cao, Z. B.; Chen, Y.; Qian, G. R.; Lu, B.; Zhou, M.; Zhou, J.
Abstract : The purpose of this study was to develop a process to recover value product from serpentine wastes using countercurrent leaching and solvent extraction. Countercurrent leaching of serpentine waste was carried out in 31% hydrochloric acid solution at 90°C using refluxing process. After countercurrent leaching of three times, acid concentration of leaching solution decreased from 5–6 to 0·5 mol L −1 and metal ion concentrations increased double. Solid residues were separated from countercurrent leaching solution by filtering process. The filtered leaching solution was extracted by mono-(2-ethylhexyl) 2-ethylhexyl phosphonate (P507 ) extractant saponified by sodium bicarbonate. The impure elements of iron, aluminum, and calcium were removed from countercurrent leaching solution. Subsequently, naphthenic acid extractant saponified withsodium carbonate was used to extract nickel from above raffinate solution, and remaining element was only magnesium in raffinate solution. Filtered solid residues were leached in 20% sodium hydroxide solution, which was used to prepare white carbon black.